Radiation therapy with neutrons and hydrons of the liver region using the MCNP code - Jarouj, Lara Kamal; Bilal, Anis; Abo Issa, Nikola (Journal of natural sciences, life and applied sciences, 2021)
CT images were read and a 3D model of the tumor was created in the liver area, Then the values ​​of the radiation dose in terms of the depth resulting from (photons, neutrons and protons) were estimated and studied using the code (MCNP) after entering the data into it.The value of the radiation dose in terms of depth and curvature in photons, neutrons and protons radiation therapy was studied, from our findings in the research we note that protons are the best option for radiation therapy for high-depth liver cancer of photons and neutrons due to the lower dose at entry compared to the dose absorbed in the tumor area and its ability to deliver a greater amount of dose of neutrons and photons to the tumor area.We note that the values reached are acceptable for the treatment of tumors at a depth close to the surface. As for a large-depth tumor, it is necessary to increase high-energy radiation doses deep in the tumor area by accelerating proton therapy to protect natural organs from high-energy radiation doses.
Keywords: MCNP Code; MCNPMatlab; The MCNP code; الماتلابaccelerators; DICOM; liver phantom